Healthcare-seeking behaviour in rural Ethiopia: evidence from clinical vignettes. Issue 2 (12th February 2014) - Mebratie, Anagaw D; Van de Poel, Ellen; Yilma, Zelalem; Abebaw, Degnet; Alemu, Getnet; Bedi, Arjun S
Abstract : Objectives: To investigate the determinants of healthcare-seeking behaviour using five context-relevant clinical vignettes. The analysis deals with three issues: whether and where to seek modern care and when to seek care. Setting: This study is set in 96 villages located in four main regions of Ethiopia. The participants of this study are 1632 rural households comprising 9455 individuals. Primary and secondary outcome measures: Probability of seeking modern care for symptoms related to acute respiratory infections/pneumonia, diarrhoea, malaria, tetanus and tuberculosis. Conditional on choosing modern healthcare, where to seek care (health post, health centre, clinic and hospital). Conditional on choosing modern healthcare, when to seek care (seek care immediately, the next day, after 2 days, between 3 days to 1 week, a week or more). Results: We find almost universal preference for modern care. Foregone care ranges from 0.6% for diarrhoea to 2.5% for tetanus. There is a systematic relationship between socioeconomic status and choice of providers mainly for adult-related conditions with households in higher consumption quintiles more likely to seek care in health centres, private/Non-Government Organization (NGO) clinics as opposed to health posts. Delays in care-seeking behaviour are apparent mainly for adult-related conditions and among poorer households. Conclusions: The analysis suggests that the lack of healthcare utilisation is not driven by the inability to recognise health problems or due to a low perceived need for modern care.